Energy dynamics in the brain: contributions of astrocytes to metabolism and pH homeostasis - Deitmer, Joachim W.; Theparambil, Shefeeq M.; Ruminot, Ivan; Noor, Sina Ibne; Becker, Holger M. (Frontiers in neuroscience, 2019)
Regulation of metabolism is complex and involves enzymes and membrane transporters, which form networks to support energy dynamics. Lactate, as a metabolic intermediate from glucose or glycogen breakdown, appears to play a major role as additional energetic substrate, which is shuttled between glycolytic and oxidative cells, both under hypoxic and normoxic conditions. Transport of lactate across the cell membrane is mediated by monocarboxylate transporters (MCTs) in cotransport with H+, which is a substrate, a signal and a modulator of metabolic processes. MCTs form a ‘transport metabolon’ with carbonic anhydrases (CAs), which not only provide a rapid equilibrium between CO2, HCO3- and H+, but, in addition, enhances lactate transport, as found in Xenopus oocytes, employed as heterologous expression system, as well as in astrocytes and cancer cells. Functional interactions between different CA isoforms and MCTs have been found to be isoform-specific, independent of the enzyme’s catalytic activity, and they require physical interaction between the proteins. Carbonic anhydrases mediate between different states of metabolic acidosis, induced by glycolysis and oxidative phosphorylation, and play a relay function in coupling pH regulation and metabolism. In the brain, metabolic processes in astrocytes appear to be linked to bicarbonate transport and to neuronal activity. Here, we focus on physiological processes of energy dynamics in astrocytes as well as on the transfer of energetic substrates to neurons.